Development and Validation of Interactive Learning Videos Based on Project Based Learning (PjBL) on Animal Characteristics Material for Grade 1 Elementary School Students - Dliyaul Haq; Maulidya Azzahra; Muhammad Dhiyaul Aulia; Putri Rahadian Dyah Kusumawati (Genderang Asa: Journal of Primary Education, 2026)
This research aims to develop and validate an interactive learning video based on Project Based Learning (PjBL) on animal characteristics material for Grade 1 elementary school students. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The product was validated by two media experts and two material experts using a Likert scale instrument. The results of media expert validation obtained a percentage of 95.6% (Very Feasible), while the material expert validation obtained a percentage of 83.5% (Feasible). Based on the validation results, the interactive learning video based on PjBL is declared feasible for use in learning, with suggestions for revision related to background music addition and improvement of PjBL syntax integration in the material presentation.